Calpain-5 gene expression in the mouse eye and brain - Schaefer, Kellie (BMC Res Notes, 2017)
OBJECTIVE: Our objective was to characterize CAPN5 gene expression in the mouse central nervous system. Mouse brain and eye sections were probed with two high-affinity RNA oligonucleotide analogs designed to bind CAPN5 RNA and one scramble, control oligonucleotide. Images were captured in brightfield. RESULTS: CAPN5 RNA probes were validated on mouse breast cancer tumor tissue. In the eye, CAPN5 was expressed in the ganglion cell, inner nuclear and outer nuclear layers of the retina. Signal could not be detected in the ciliary body or the iris because of the high density of melanin. In the brain, CAPN5 was expressed in the granule cell layers of the hippocampus and cerebellum. There was scattered expression in pons. The visual cortex showed faint signal. Most signal in the brain was in a punctate pattern.